NOUN PHRASE PATTERNS ANALYSIS ON THE ENGLISH TRANSLATION OF SURAH AL-MULK BY MUFTI TAQI USMANI - Dina Lestari; Abdur Rofik (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2023)
This study is aimed for analyzing: (1) the noun phrase patterns, and (2) the most dominant noun phrase patterns used on the English Translation of surah Al-Mulk by Mufti Taqi Usmani, with uses qualitative method. Reading, identifying, classifying, presenting, are the process of collecting data. Method of the analyzing data is drawing the diagrams, analyzing, describing, finding, and concluding. Theory of Tree Diagrams by Diane Bornstein (1977) and theory of noun phrase by John Eastwood (1994) are the theory that used to analyzing the data. The result of the study: (1) the noun phrase patterns found on the data are noun phrase that consists of one word, determiners, prepositional phrase, adjective, noun, clause; (2) the most dominant noun phrase patterns used on the data is noun phrase that consists of one word.